Dual Roles of Working Women in the Formal Sector (Case Study on Female Workers Who Leave Children at Day Care "Paradise Baby" South Jakarta) - Syamsiah Badruddin; Monita Rahayu (IJESS International Journal of Education and Social Science, 2021)
This study discusses "Dual Roles of Women Workers in the Formal Sector (Case Study on Female Workers Who Leave Children in Day Care "Paradise Baby" South Jakarta)". The aims of this study are (1) to see the role of working women in the formal sector in their families, (2) to find out the problem of the dual role of working mothers, (3) how to overcome the problem of the dual role of working mothers. The method used in this research is descriptive qualitative research method, so that it will get descriptive data in the form of words and behavior in depth. The research subjects are women who have multiple roles and work in the formal sector. Collecting data using the method of observation, in-depth interviews and documentation. This research was analyzed using Functional Structural Theory. The results of this study indicate: (1) Working women in carrying out their role at home, namely in raising children by entrusting their children to Day Care, in this case Day Care acts as a substitute family when working women are busy working. Then women workers in carrying out their roles in the formal sector, namely by following the applicable regulations in the workplace and continuing to work according to their demands and professions, (2) The problem faced by the dual role of working mothers is the lack of time for family and society, (3) In overcoming The problem of the dual role of working mothers is that husbands help with housework which can ease the burden on women.